Reducing Postsurgical Exudate in Breast Cancer Patients by Using San Huang Decoction to Ameliorate Inflammatory Status: A Prospective Clinical Trial - Zhu, Z. Y.; Xue, J. X.; Yu, L. X.; Bian, W. H.; Zhang, Y. F.; Sohn, K. C.; Shin, I. H.; Yao, C. (Current oncology (Toronto), 2018)
Background Reducing inflammatory factors in wound exudate is a promising treatment approach for healing wounds in postsurgical breast cancer patients. Traditional Chinese Medicine (tcm) treatments have been shown to be beneficial and safe for optimal regulation of oxidative stress during the postoperative period. In the present clinical trial, we evaluated the effectiveness of a promising Chinese herbal formula, San Huang decoction [shd (Radix astragali, Radix et rhizoma rhei, and Rhizoma curcuma longa, 3:1:1; supplemental Table 1)], on wound inflammatory response after mastectomy. Methods The study randomized 30 patients with breast cancer who fulfilled the inclusion and exclusion criteria to either a treatment (n = 15) or a control group (n = 15). Patients in the treatment group received liquid shd, taken twice daily with or without food. Treatment was given for 1 day before surgery and for 7 days postoperatively. Participants in the control group received a placebo on the same schedule as the treatment group. Outcomes measured in every subject included clinical tcm and wound inflammation symptom scores, daily and total amounts of drainage fluid, and levels of inflammatory factors in the exudate [tumour necrosis factor α (tnf-α), interleukins 6 (il-6), 8 (il-8), and 2R (il-2R), human C-reactive protein (crp)] at 2 h and on days 1, 3, and 7 postoperatively. Results The total amount of drainage fluid over 7 days was significantly lower in the treatment group (572.20 ± 93.95 mL) than in the control group (700.40 ± 107.38 mL). The tcm symptom score was also lower in treatment group (day 7: 1.87 ± 0.83 vs. 4.80 ± 3.61, p = 0.049), as was the inflammatory symptom score (day 7: 0.67 ± 0.72 vs. 3.67 ± 2.50, p = 0.001). Levels of tnf-α, il-6, il-8, il-2R, and crp in drainage fluid were significantly lower with shd treatment. Conclusions Perioperative treatment with shd effectively lessened postoperative exudate and ameliorated inflammatory symptoms in patients who underwent surgery for breast cancer.